The role of Big Data in Climate research - Andreea-Mihaela NICULAE; Alin Gabriel VADUVA (Database Systems Journal)
Combining big-data analytics, text mining, NLP, and Latent Dirichlet Allocation, this study reviews 7,145 open-access climate-change publications (2011-2022). Key research themes include urban health, smart technologies, and algorithmic modelling. While big-data applications grew steadily to 2022, a decline in 2023 suggests shifting priorities. Sentiment analysis shows predominantly neutral tones, and the integrated approach offers insights into evolving climate-research trends.